A Comparative Survey of Centralised and Decentralised Identity Management Systems: Analysing Scalability, Security, and Feasibility - Aviral Goel; Yogachandran Rahulamathavan (Future Internet)
Traditional identity management (IdM) solutions based on centralised protocols, such as Lightweight Directory Access Protocol (LDAP) and Security Assertion Markup Language (SAML), are where a central authority manages all the processes. This risks a single point of failure and other vulnerabilities. In response, decentralised techniques like blockchain and decentralised identities (DIDs) are being explored. This review paper performs a comparison of popular decentralised identity management (DIM) protocols, such as self-sovereign identity (SSI), against traditional centralised approaches such as LDAP and SAML. These decentralised identity management systems are being developed, keeping users’ identity data as its highest priority. Additionally, this method eliminates the need for a central authority to manage and secure the system. To further explore the potential of decentralised identity management, this study delves into popular blockchain-based decentralised identity management systems such as uPort, Sovrin, EverID, Blockstack, ShoCard, and Hyperledger Indy. We analyse their underlying principles and compare them with the well-established centralised identity management solutions, focusing on key aspects such as scalability, security, and feasibility. However, despite their benefits and several worthy developments in this field, decentralised approaches are still not widely used. Through this study, we investigate both centralised and decentralised methods and review their strengths and weaknesses. By reviewing multiple research papers, this survey aims to provide an understanding and aid in selecting the most suitable identity management system for different use cases.